EXPERT SYSTEM FOR DIAGNOSING CAT DISEASES USING FORWARD CHAINING METHOD ON TELEGRAM BOT - Aprianto, A’inur Kholiz; Ipung Permadi; Bangun Wijayanto (Informatika, Universitas Jenderal Soedirman, 2023)
Cats are one of the popular pets kept in Indonesia. On the other hand, there is a potential risk of disease transmission from cats to humans. This research builds an expert system for diagnosing cat diseases based on the symptoms experienced using the forward chaining method. The expert system consists of two main components: the development environment and the consultation environment. In this study, these two components of the expert system are separated into two different platforms. The development environment runs on a website platform, while the consultation environment operates on a Telegram bot platform. System development uses the Expert System Development Life Cycle (ESDLC) development model. This model has six stages, namely, the assessment stage, the knowledge acquisition stage, the design stage, the testing stage, the documentation stage and the maintenance stage. As a result, it assists the general public in performing initial diagnoses of cat diseases.